1991
DOI: 10.1007/bf01369806
|View full text |Cite
|
Sign up to set email alerts
|

Inter-alpha-trypsin inhibitor (ITI): A useful genetic system in paternity testing. Evidence for polymorphic occurrence ofITI*3 and existence of a new allele,ITI*4

Abstract: The genetic polymorphism of human inter-alpha-trypsin inhibitor (ITI) has been investigated in sialidase-treated samples by isoelectric focusing on polyacrylamide gels with a pH range 3.5-9.5 followed by passive blotting with enzyme immunoassay. In 400 blood donors from western Japan, 8 simplified band patterns were observed, 6 of which could be explained by the previously described 3 polymorphic alleles, ITI*1, ITI*2, and ITI*3. The others were products of a new and rare fourth allele designated ITI*4, whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This simple mode of Mendelian inheritance has been confirmed by Luckenbach et al (1991), who have investigated the ITI polymorphism in formal genetic and linkage analysis. It has been shown that the ITI allele and phenotype frequency distribution is significantly different in European, Asian and African populations (Vogt et al a, 1992Yuasa et al 1991). The ITI system is, thus, a useful marker for population genetics and forensic studies.…”
Section: Introductionmentioning
confidence: 98%
“…This simple mode of Mendelian inheritance has been confirmed by Luckenbach et al (1991), who have investigated the ITI polymorphism in formal genetic and linkage analysis. It has been shown that the ITI allele and phenotype frequency distribution is significantly different in European, Asian and African populations (Vogt et al a, 1992Yuasa et al 1991). The ITI system is, thus, a useful marker for population genetics and forensic studies.…”
Section: Introductionmentioning
confidence: 98%
“…Restraction fragment length polymorphisms (RFLPs) of ITI genes were reported [3][4][5][6][7], and the ITI polymorphism of serum protein was first described by Vogt and Cleve [8]. The [8][9][10][11][12] and recently, Vogt et al [13] reported that ITI protein polymorphism may be controlled by the gene coding for the ITI heavy chain H1.…”
Section: Introductionmentioning
confidence: 99%
“…ITI is controlled by 3 common alleles ITI* 1, ITI*2 and ITI*3. Recently, additional alleles ITI*4, ITI*5 and ITI*6 have been reported [5][6][7].…”
Section: Introductionmentioning
confidence: 99%